DEVELOPMENT MATHEMATIC MODULE OF ALGEBRAIC FORM MATERIAL FOR STUDENTS IN GRADE VII SMP/MTS WITH A SCIENTIFIC APPROACH - Marsiska Isnaini; Sumargiyani Sumargiyani (Universitas Ahmad Dahlan, 2018)
The availability of learning materials using a scientific approach that can facilitate students to learn actively and independently is still limited. The mathematic module material form of algebra is one of the alternative materials that can be used to facilitate students in an independent study actively. This research aims to develop a mathematical module of algebraic form material for students in grade VII SMP/MTs with a scientific approach and test the feasibility of the module. This type of research is research development, a mathematical module of algebraic form material for students in grade VII SMP/MTs with a scientific approach. In developing this module refers to researcher development model ADDIE that includes five stages, namely Analysis, Design, Development, Implementation, and Evaluation. The instruments used in the study of this form of assessment sheets for expert assessment sheets for the material, media experts, and student response now. This is a subject matter, media experts, and students of State Junior High School 15 Yogyakarta (SMP Negeri 15 Yogyakarta) and Muhammadiyah Islamic Junior High School Karangkajen (Mts Muhammadiyah Karangkajen). Using qualitative analysis, technical data analysis is converted into a cumulative value scale Likert—data collection techniques in the form of an interview and question form. The results of this research and development show that mathematics developed modules are included in the category of very good based on the assessment by the expert question form the material with a score of 102.33; question form assessment by media expert with score 74.67; and the average student response results in this study was 86,52. The assessment results indicate that the mathematical module of algebraic from material for students in grade VII SMP/MTs with a scientific approach worthy of use in the learning process.